Modern challenges facing electric vehicle adoption: a review of barriers to adoption, supply chain challenges, and equity - Hala Alshahapy; Joe F Bozeman III; Sanya Carley; Destenie Nock; Daniel Matisoff (Environmental Research Letters)
The automotive industry’s shift to electric vehicles (EVs) faces persistent barriers in pricing, financing, and charging infrastructure, particularly affecting low-income and disadvantaged individuals. These hurdles pose challenges to achieving US decarbonization goals and hinder the development of a sustainable and electrified transportation sector. Global disruptions in the supply chain, driven by the pandemic and geopolitical tensions, exacerbate these challenges, keeping EV purchase prices elevated. Key disruptors include critical mineral scarcity, semiconductor shortages, and international trade and COVID-19-related restrictions, complicating efforts to overcome adoption hurdles. Conducting a systematic review using Google Scholar and ScienceDirect, we focused on articles related to EV supply chain disruptions, equity, and adoption barriers published in English post-2009. We analyzed 130 articles for topical focus and key findings. Our exploration reveals insights into the challenges of electrifying the transportation sector while addressing equity concerns. Proposing a systemic equity framework, we advocate for the simultaneous and effective administration of resources, policies, and cultural considerations for systematically marginalized communities. This holistic approach aims to navigate the complexities of the EV supply chain, fostering a future marked by equitable transport electrification. The intersection of equity issues with supply chain challenges emphasizes the timeliness and importance of this academic examination. Our contribution to the ongoing discourse on achieving a sustainable and inclusive transition to EVs delves into the dynamics of these challenges, highlighting the need for comprehensive solutions.